(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This study investigates cultural memory as a literary category in contemporary fiction, examining how novels written between 1987 and 2020 employ narrative strategies to construct, negotiate, and transmit collective memories of historically significant events. Drawing on the theoretical frameworks of Jan Assmann, Aleida Assmann, Pierre Nora, and Astrid Erll, the research analyzes a corpus of 15 critically acclaimed novels from diverse literary traditions to identify the principal textual mechanisms through which cultural memory is inscribed in fictional narrative. A qualitative content analysis of the selected works revealed four dominant literary strategies: palimpsestic layering of temporal planes, intertextual dialogue with archival and testimonial sources, the deployment of unreliable or fragmented narration as a mimesis of traumatic remembrance, and the use of material objects and spatial settings as mnemonic anchors. The findings demonstrate that contemporary fiction functions not merely as a reflection of pre-existing cultural memories but as an active medium of memory production, capable of reshaping collective understandings of the past through aesthetic and narrative innovation. These results contribute to the growing interdisciplinary dialogue between memory studies and literary criticism and carry implications for the teaching of literature as a form of cultural and historical engagement.